Evaluation of Inhibition Steroid Effect by Diazinon Pollutions on Ovarium and Cortex Adrenal Glands of the Animal Model - Sufiriyanto, Sufiriyanto; Indradji, M (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2002)
A study was conducted to influence of the diazinon pollutions effect to histopathologic change examination of ovarium and cortex adrenal glands the rat (Rattus norvegicus) caused of steroid inhibition metabolism. The treatment consisted of four level doses of diazinon as follows 0, 50, 100 and 200 ppm for 40 days, in drinking water. The microscopic examination result showed that vacuolar degeneration change in surrounding corpus atreticum and hemorrhagic lesion on interstitial cell of ovarian, in starting dose 50 ppm and then, the swollen cells and congestive lesion of cortex adrenal glands, in starting dose 100 ppm. (Animal Production 4(2): 101-111 (2002)Â Key words : Diazinon, Steroid, Cortex Adrenal Glands